Chapter 43: Materials analysis of ceramics - Erb-Satullo, Nathaniel L. (Wiley, 2023)
The versatility and geological ubiquity of clay materials have meant that humans have adapted it to a wide range of different purposes, from building materials to tools for storage, transport, cooking, and eating. Archaeological ceramics range from mundane everyday wares to exquisite pieces of craftsmanship available only to the highest elites. Ceramic ethnoarchaeology has documented a wide range of approaches to clay processing, involving the removal and addition of constituents, as well as homogenization and transformation of raw materials through ageing or ‘souring’ of clays to improve their properties. Most laboratory analyses of ceramic materials can be grouped into three broad categories: compositional analyses, microstructural analyses, and macrostructural analyses. The presence of optical activity in the clay groundmass, when viewed in thin section under crosspolars, suggests a firing process that preserved the crystalline structure of clay minerals and did not result in extensive vitrification.